Viltolarsen in Japanese Duchenne muscular dystrophy patients: A phase 1/2 study. Issue 12 (7th December 2020) - Komaki, Hirofumi; Takeshima, Yasuhiro; Matsumura, Tsuyoshi; Ozasa, Shiro; Funato, Michinori; Takeshita, Eri; Iwata, Yasuyuki; Yajima, Hiroyuki; Egawa, Yoichi; Toramoto, Takuya; Tajima, Masaya; Takeda, Shinichi
Abstract: Objective: The novel morpholino antisense oligonucleotide viltolarsen targets exon 53 of the dystrophin gene, and could be an effective treatment for patients with Duchenne muscular dystrophy (DMD). We investigated viltolarsen's ability to induce dystrophin expression and examined its safety in DMD patients. Methods: In this open‐label, multicenter, parallel‐group, phase 1/2, exploratory study, 16 ambulant and nonambulant males aged 5–12 years with DMD received viltolarsen 40 or 80 mg/kg/week via intravenous infusion for 24 weeks. Primary endpoints were dystrophin expression and exon 53 skipping levels. Results: In western blot analysis, mean changes in dystrophin expression (% normal) from baseline to Weeks 12 and 24 were − 1.21 ( P = 0.5136) and 1.46 ( P = 0.1636), respectively, in the 40 mg/kg group, and 0.76 ( P = 0.2367) and 4.81 ( P = 0.0536), respectively, in the 80 mg/kg group. The increase in mean dystrophin level at Weeks 12 and 24 was significant in the 80 mg/kg group (2.78%; P = 0.0364). Patients receiving 80 mg/kg showed a higher mean exon 53 skipping level (42.4%) than those receiving 40 mg/kg (21.8%). All adverse events were judged to be mild or moderate in intensity and none led to study discontinuation. Interpretation: Treatment with viltolarsen 40 or 80 mg/kg elicited an increasing trend in dystrophin expression and exon 53 skipping levels, and was safe and well tolerated. The decline in motor function appeared less marked in patients with higher dystrophin levels; this may warrant further investigation. This study supports the potential clinical benefit of viltolarsen.